Política judiciária nacional de tratamento adequado dos conflitos de interesses: um estudo de caso sobre a mediação e a conciliação no 1º Centro Judiciário de Solução de Conflitos do Fórum Desembargador Sarney Costa - COELHO, Washington Souza (2019)
This paper analyzes the effects of the Judicial Policy on the Treatment of Conflicts of Interest instituted by Resolution 125/2010, as well as verifying the changes arising from the New Code of Civil Procedure, the Mediation Law and the use of Appropriate Means of Resolution Conflicts after these normative milestones, for this, the application of these means in the Court of Justice of the State of Maranhão is verified, as well as, it performs an analysis of the participation and contribution of the institutional subjects and propellers of the judicial policy within directives integrated for the purpose to analyze whether there has been a reduction in conflicts of interest and how this occurs. Finally, it is carried out by means of the qualitative method of case study, having as object the 1 st. Cejusc of the Judicial Council of Sarney Costa, which integrates the structure of the Judicial Power of Maranhão, where it was sought to analyze the level of user satisfaction, if the means proposed by the CNJ were actually implemented and how the conflict facilitators act.